FORGIVENESS THERAPY TO INCREASE THE MEANING OF LIFE AMONG INMATES IN - Zuanny, Iyulen Pebry; Subandhi, Subandhi - (Psikoislamedia: Jurnal Psikologi, 2016)
Inmates experiences various condition and change in facing her life. Beside experiencing burden physically because of obstacle to maintain prior activity, many inmates has experienced psychological burden. Feeling guilty, shame, hostility, regret, despair, and having negative view about theirselves lead inmates experiencing anxiety, depression, and even suicidal act as a consequence of feeling about their lives as meaningless. Forgiveness therapy offer understanding and adaptive coping skill so inmates is able to reconcile with herself, other person and stressful situation, also reduce various negative emotions in such a way that meaning of life increases. The study is quasi experiment research will use one group with double pre-test and post-test engaging7 women inmates, in their 23-45 years old with embezzlement and fraud case. This study aimed to see whether forgiveness therapy could improve the meaning of life of woman inmates in prisons.Data analyzed using repeated measure ANOVAand supported by descriptive analysis. The result showed that forgiveness therapy was significant in increase woman inmates meaning of life after therapy.